Peningkatan Pengetahuan dan Sikap Masyarakat terhadap Upaya Pencegahan dan Pengendalian Covid-19 di Desa Kejawar Banyumas - Hening Pratiwi; Beti Pudyastuti; Warsinah; Nia Kurnia Sholihat; Triyadi Hendra; Nur Amalia Choironi; M. Salman Fareza (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) better known as Covid-19 is a new type of coronavirus that transmitted to humans. This virus is contagious quickly and has spread to almost all countries, including Indonesia, in just a few months. Public awareness and behavior are needed to prevent and control COVID-19. Objective: This activity aimed to increase public knowledge and attitudes to actively participate in preventing and controlling the transmission of Covid 19. Method: The implementation of this activity begins with the process of evaluating the level of knowledge and attitudes of PKK cadres regarding the prevention and control of Covid-19 by conducting a pre-test using a questionnaire. Then, the team provided education about the prevention and control of Covid-19 by using appropriate media. This activity was carried out using the transfer & sharing method of knowledge by using aids of audiovisual media and leaflets. Besides being open for discussion sessions, questions, and answers related to Covid-19. Result: The results showed an increase in respondents' knowledge before and after education by as much as 47%, while the attitudes of respondents showed an increase before and after education by as much as 47%. Conclusion: We concluded that providing education related to Covid 19 could increase people's knowledge and attitudes.